2016
DOI: 10.1002/pbc.26395
|View full text |Cite
|
Sign up to set email alerts
|

Delayed elimination of high-dose methotrexate and use of carboxypeptidase G2 in pediatric patients during treatment for acute lymphoblastic leukemia

Abstract: CPDG administration is highly effective as rescue in case of delayed Mtx clearance. Subsequent HDMtx courses could be administered without events in most of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 28 publications
3
84
0
Order By: Relevance
“…Alkalinization and vigorous hydration reduce the risk of significant nephrotoxicity with HD-MTX, but approximately 3% of patients will experience severe renal toxicity that will further compromise MTX clearance 125128 . The nephrotoxicity is likely to be related to precipitation of MTX crystals in the kidneys and this is partly due to insufficient hydration and alkalization 129, 130 .…”
Section: Hd-mtx-related Nephrotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Alkalinization and vigorous hydration reduce the risk of significant nephrotoxicity with HD-MTX, but approximately 3% of patients will experience severe renal toxicity that will further compromise MTX clearance 125128 . The nephrotoxicity is likely to be related to precipitation of MTX crystals in the kidneys and this is partly due to insufficient hydration and alkalization 129, 130 .…”
Section: Hd-mtx-related Nephrotoxicitymentioning
confidence: 99%
“…Plasma creatinine usually peaks within a few days after initiation of the HD-MTX infusion and returns to baseline after a few weeks. Nearly all patients will subsequently tolerate full-dose HD-MTX without recurrent nephrotoxicity 127, 128 . Higher doses of folinic acid, adjusted by the plasma MTX levels, are essential to limit the risk of life-threatening myelosuppression and mucositis, but whether over-rescue could increase the risk of relapse remains an unsolved challenge 131133 .…”
Section: Hd-mtx-related Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of having severely or moderately delayed MTX elimination was strikingly higher in the first HD‐MTX infusion compared with the HD‐MTX infusions given later in the consolidation and maintenance treatment phases. Others have similarly found that the MTX clearance is lowest in the first HD‐MTX infusion, and it was recently shown that treatment with carboxypeptidase for patients with severely delayed MTX elimination was primarily needed in the first HD‐MTX infusion given to patients with ALL . The first HD‐MTX infusion was given shortly after the induction therapy, suggesting that factors such as tumor lysis or nephrotoxicity during the induction phase could have reduced the kidney's ability to eliminate MTX in the first HD‐MTX infusion.…”
Section: Discussionmentioning
confidence: 99%
“…High‐dose MTX (HD‐MTX) 1–8 g/m² is used to overcome cellular resistance and promote transport into pharmacological sanctuaries (e.g., testes and central nervous system [CNS]) . The MTX elimination varies significantly between HD‐MTX courses, and extremely slow MTX elimination is seen in up to 5% of patients with ALL . The variation in MTX elimination is difficult to predict and can only, to some extent, be explained by age, gender, treatment protocol, and germline DNA polymorphisms …”
Section: Introductionmentioning
confidence: 99%